2020 International Seminar on Application for Technology of Information and Communication (iSemantic) 2020
DOI: 10.1109/isemantic50169.2020.9234251
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perception of Online Learning in Covid-19 Pandemic : A Case Study in a Translation Course

Abstract: 2 0 20 In te rn a tio n a l S em inar on A p p lic a tio n fo r T echn ology o f In fo rm a tio n and C o m m u n ica tio n (iS em antic)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 6 publications
(1 reference statement)
2
36
1
Order By: Relevance
“…In accordance with [38], technology and service play a primary role in promoting students' e-learning. Moreover, further research confirms a significant positive impact of technology and service on the e-learning of students [39]- [40]. Additionally, the study findings also confirmed that the quality of e-service contributed positively to promoting the e-learning of students.…”
Section: Resultssupporting
confidence: 70%
“…In accordance with [38], technology and service play a primary role in promoting students' e-learning. Moreover, further research confirms a significant positive impact of technology and service on the e-learning of students [39]- [40]. Additionally, the study findings also confirmed that the quality of e-service contributed positively to promoting the e-learning of students.…”
Section: Resultssupporting
confidence: 70%
“…Online learning for STKIP Pamane Talino's English Language Study Program requires more friendly platforms to increase student participation. Then, Nugroho, et al, (2020) showed that students' positive perception of the use of Omega T and Google classroom in Dian Nuswantoro University S1 English Study Program is a translation course during COVID-19.…”
Section: B Review Of Literaturementioning
confidence: 99%
“…Although there was an 80 % negative review of the online lectured class, a 90 % positive review was given to the utilisation of Google Classroom and OmegaT application. This shows that futuristic e-learning could be effective with modern IT solutions [7]. While using a quantitative method to understand the perspective of students in e-learning, Loh et al [8] found that students felt comfortable due to the flexibility of e-learning, allowing progress at their own pace.…”
Section: The Perceived Satisfaction With Emergency Remote Teaching (Ert) Amidst Covid-19mentioning
confidence: 99%
“…This poses a dilemma for practice-based activities, such as laboratory practice, translation courses, and others. Nugroho et al [7] used a qualitative structure to determine the perception of students in a specific translation class. Although there was an 80 % negative review of the online lectured class, a 90 % positive review was given to the utilisation of Google Classroom and OmegaT application.…”
Section: The Perceived Satisfaction With Emergency Remote Teaching (Ert) Amidst Covid-19mentioning
confidence: 99%